Страховий захист індивідуума у процесі рекреації - Охріменко, О.О. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье акцентировано внимание на роли и месте страхования в социальной защите туристов. Обобщен законодательный опыт личного страхования туристов, которые отбывают за границу. Дана оценка эффективности страхования с позиций социальной защиты населения. In article the attention on a role and place of insurance in social defence of tourists is accented. The legislative experience of the personal insurance of tourists which depart foreign country is generalized. The estimation of efficiency of insurance from positions of social defence of population is given.